Financial Technology Literacy Impact on Gen-Z in Indonesia - Putra Utama, Doni; Dian Sumarna, Alfonsa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this study Financial Technology Literacy Impact on Gen-Z in Indonesia" is to investigate and understand the impact of financial technology literacy (FinTech), and trust in the financial behavior of Generation Z in Indonesia. This study used quantitative methods, where respondents came from adolescents with an age range of 17 years to 21 years on two campuses in Batam. Using random sampling in the distribution of questionnaires, out of 100 questionnaires distributed, only 37 questionnaires were returned, so the results of 37 questionnaires were used for data analysis. Data analysis techniques are assisted by using SPSS 24 to obtain results to be interpreted by looking at the relationship between variables in this study. By using respondents who came from adolescents with an age range of 17 years to 21 years in two campuses in Batam, it was stated that the variables in this study that there was a positive and significant influence between FinTech variables and Generation Z, there was a positive and significant influence between Trust variables and Generation Z, and the results of 32.4% then there was a positive and significant influence due to these three variables,  The rest is not discussed in this study. The recommendation in this study is that the results of this study were conducted to adolescents who can be said to be Generation Z with the object of two campuses in Batam, so it is still necessary to develop by other researchers in using and adding variables to produce research, these results provide a form of real contribution in financial research.